Surgical management aspect of the patient with clear cell renal cell carcinoma metastasis to the upper lip - a case report - Gnatek, Adrian; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article describes the case of a 49–year-old patient with clear cell renal cell carcinoma metastasis to the upper lip that has undergone the procedure of excision of the metastatic lesion with carbon dioxide surgical laser.